Coupling of size‐exclusion chromatography with electrospray ionization charge‐detection mass spectrometry for the characterization of synthetic polymers of ultra‐high molar mass. (2nd December 2015) - Viodé, Arthur; Dagany, Xavier; Kerleroux, Michel; Dugourd, Philippe; Doussineau, Tristan; Charles, Laurence; Antoine, Rodolphe
Abstract : Rationale: Coupling size‐exclusion chromatography (SEC) with mass spectrometry (MS) allowed generation of a SEC calibration curve based on the analyte itself, which is more reliable than calibration based on non‐related standards and faster than the use of the multiple detection mode. However, such SEC/MS couplings were limited to rather small synthetic polymers. Methods: Based on the concept of image current detection, charge‐detection mass spectrometry (CDMS) coupled to electrospray ionization (ESI) is a useful method for weighing macro‐ions from compounds with masses higher than one megadalton (MDa). Using columns designed to allow analysis of synthetic polymers of over 15 million Dalton in mass, performance of the SEC/ESI‐CDMS coupling was evaluated for polyacrylamide (PAM, 5–6 MDa) and a poly(2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid) (PAMPS, 2 MDa). Results: The SEC/ESI‐CDMS profiles were first compared with SEC‐UV profiles: the systematic shift in retention time was assigned to the slightly different geometries of the two instrumental systems. The SEC/ESI‐CDMS data were then compared with results obtained after the direct infusion of each sample into the ESI source. Both the shape of the molecular weight distribution and the mass values were similar with or without separation prior to ESI, and these values were consistent with data provided by the sample supplier. Conclusions: SEC/MS incorporating an online ESI‐CDMS coupling was shown to be a rapid and efficient technique for the analysis of water‐soluble synthetic polymers with ultra‐high molecular mass in the megadalton range. The coupling also afforded an attractive solution for SEC calibration without the use of external standards. Copyright © 2015 John Wiley & Sons, Ltd.